METAPHOR AND STRUCTURAL COMPOSITION - Ulugova Shokhida Shokhrukhovna; Ganiyeva Shaxrizoda Gayratjonova (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Abstract. This article provides detailed information on the nature and types of metaphor.The article introduces the explanatory dictionary of the word metaphorical and analysis several metaphorical terms in the Uzbek language.And, of course, we will see how it is used in sentences,what artistic colouring it gives to sentences when it is used.It also sheds light on the specific characteristics and meanings of "metaphor" in our culture.